In vitro DNA/RNA Adductomics to Confirm DNA Damage Caused by Benzo[a]pyrene in the Hep G2 Cell Line - Takeshita, Toshihide; Kanaly, Robert A. (Frontiers in Chemistry, 2019)
In the development of new chemical substances, genetic toxicity evaluations are a high priority for safety risk management. Evaluation of the possibility of compound carcinogenicity with accuracy and at reasonable cost in the early stages of development by in vitro techniques is preferred. Currently, DNA damage-related in vitro genotoxicity tests are widely-used screening tools after which next generation toxicity testing may be applied to confirm DNA damage. DNA adductomics may be used to evaluate DNA damage in vitro, however confirmation of DNA adduct identities through comparison to authentic standards may be time-consuming and expensive processes. Considering this, a streamlined method for confirming putative DNA adducts that are detected by DNA adductomics may be useful. With this aim, in vitro DNA adductome methods in conjunction with in vitro RNA adductome methods may be proposed as a DNA adductome verification approach by which to eliminate false positive annotations. Such an approach was evaluated by conducting in vitro assays whereby Hep G2 cell lines that were exposed to or not exposed to benzo[a]pyrene were digested to their respective 2'-deoxynucleosides or ribonucleosides and analyzed by liquid chromatography electrospray ionization tandem mass spectrometry (LC/ESI-MS/MS) by comparative DNA and RNA adductomics through neutral loss targeting of the [M + H]+ > [M + H - 116]+ or [M + H]+ > [M + H - 132]+ transitions over predetermined ranges. Comparisons of DNA adductome maps revealed putative DNA adducts that were detected in exposed cells but not in unexposed cells. Similarly, comparisons of RNA adductome maps revealed putative RNA adducts in exposed cells but not in unexposed cells. Taken together these experiments revealed that analogous forms of putative damage had occurred in both DNA and RNA which supported that putative DNA adducts detected by DNA adductomics were DNA adducts. High resolution mass spectrometry (HRMS) was utilized to confirm that putative nucleic acid adducts detected in both DNA and RNA were derived from benzo[a]pyrene exposure and these putative adducts were identified as 7,8-dihydroxy-9,10-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene- (B[a]PDE)-type adducts. Overall, this study demonstrates the usefulness of utilizing DNA/RNA adductomics to screen for nucleic acid damage.